Validating the Social Dimension of the Village Index in Supporting Village Tourism Development: A Confirmatory Factor Analysis - Ayu Esteka Sari; Gampo Haryono; Iin Syofia Yandra; Shobhi Al-Ghifari Azhary; Elsa Maiyora (International Journal of Business and Quality Research, 2026)
This study aims to validate the social dimension of the Village Index in supporting village tourism development using Confirmatory Factor Analysis (CFA). The social dimension is essential for village tourism, as tourism activities depend on community participation, social cohesion, security, and the availability of community facilities. This research employs a quantitative confirmatory approach using secondary data derived from the Village Index. The population consists of 285 villages in Kerinci Regency, and a total sampling (census) technique is applied. The results show that the correlation between community activities and community facilities is very strong (r = 0.875), indicating a close interrelationship between social engagement and social infrastructure. These findings confirm that the social dimension of the Village Index is a valid and reliable framework for assessing social readiness in village tourism development. The study provides an empirically validated measurement model and offers policy-relevant insights for strengthening sustainable village tourism aligned with the Sustainable Development Goals (SDGs), particularly SDG 8, SDG 11, and SDG 16.